The Influence of Digital Marketing and Consumer Behavior on Purchase Decisions at Mega Akbar Regency Housing - Naja Jessyka Maulani Putri; Ely Siswanto; Ita Prihatining Wilujeng (Dinasti International Journal of Economics, Finance & Accounting, 2025)
In today's digital era, marketing strategies in the property industry have undergone significant changes. Digital marketing has become a primary tool for developers to reach potential buyers more easily and widely. However, besides digital marketing strategies, consumer behavior also plays a crucial role in determining home purchase decisions. Buying property is a major decision influenced by various factors, such as psychological, social, economic, and personal experiences. This study aims to determine the extent of the influence of digital marketing and consumer behavior on home purchase decisions at Mega Akbar Regency Housing. Using a quantitative method, this research involves 70 respondents who have completed a questionnaire. The collected data is then analyzed using various statistical tests, including multiple linear regression, correlation, and significance tests with the help of SPSS. The results indicate that digital marketing and consumer behavior significantly influence purchase decisions. However, consumer behavior has a more dominant influence compared to digital marketing. This means that while digital marketing strategies are highly effective in attracting potential buyers' attention, psychological factors, recommendations from others, and how consumers search for and compare information play a more decisive role in their final decision to purchase a home.